Implementasi QRIS dan GoBiz untuk Meningkatkan Daya Saing Warung Miedes Pring Wulung di Kabupaten Bantul - Nuraini, Riana Ike; Wulandari, Ika (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2024)
The development of digital technology has opened new opportunities for traditional culinary businesses to grow, especially through the implementation of digital payment systems and online marketing platforms. This community service research aims to analyze and implement QRIS (Quick Response Code Indonesian Standard) and GoBiz at Warung Miedes Pring Wulung in Bantul Regency, focusing on increasing business competitiveness. The method used is a participatory approach through training, mentoring, and direct implementation. The activity was carried out for 3 months involving the owner. The results of the service show a significant increase in transaction efficiency and marketing reach. QRIS implementation increased transaction speed by 68% and reduced recording errors by 92%. Meanwhile, the use of GoBiz expanded marketing reach to a radius of 7 km and increased online orders by 156% in the first 2 months. The main challenges faced include technology adaptation by senior employees and order management during peak hours. Recommended strategies include ongoing training, digital menu optimization, and integration of order management systems. In conclusion, the implementation of QRIS and GoBiz has proven effective in increasing the competitiveness of Warung Miedes Pring Wulung, providing a strong foundation for business growth in the digital era.